Superfluid-Cooled Transmon Qubits under Optical Excitation - Chunzhen Li; Yufeng Wu; Manuel C. C. Pace; Matthew D. LaHaye; Michael Senatore; Hong X. Tang (PRX Quantum, 2025)
Microwave-to-optical quantum state transfer enables the interconnection of remote superconducting quantum processors via optical-fiber links. Achieving high conversion efficiency necessitates an intense optical pump, yet direct optical exposure of superconducting circuits often degrades their performance. Efficient and fast thermalization of superconducting qubits is therefore essential. To achieve this, we immerse a laser-illuminated transmon qubit in superfluid helium-4 and investigate its behavior. We observe that the qubit recovers significantly faster in superfluid helium than in vacuum, with an improvement in power handling by over 10 dB. This enhanced cooling capacity supports higher optical pump powers, shortening recovery times after high-power optical pulses. These findings open a promising pathway for future efficient implementation of microwave-to-optical quantum transduction devices.